Progressive Muscle Relaxation Education to Reduce Stress Levels Among Students at Kesatrian 2 Health Vocational School, Purwokerto - Pipit Alfia Marlinah; Tri Sumarni; Indri Heri Susanti (FKM UIN Sumatera Utara Medan, 2026)
Adolescents in Indonesia are vulnerable to academic stress, particularly vocational high school students who face learning demands, practical examinations, and environmental pressures at school. Unmanaged stress may affect concentration, emotional stability, and physical health. Progressive muscle relaxation (PMR) is a simple and effective technique that can help reduce stress levels among adolescents. The purpose of this service was to provide education on progressive muscle relaxation techniques to reduce stress levels among students. This public service was conducted at SMK Kesehatan Kesatrian 2 Purwokerto in two meetings involving 34 twelfth-grade students from the Layanan Penunjang Keperawatan dan Caregiving (LPKC) program. The activities included lectures and demonstrations on progressive muscle relaxation techniques. Stress levels were measured using the Adolescence Stress Scale (ADOSS), consisting of 16 items scored from 0 (“never”) to 3 (“almost every day”). Students’ knowledge and stress levels were assessed before and after the educational intervention, followed by independent practice for seven days. The results showed an increase in students’ knowledge by 35.14% and a decrease in stress levels by 20.44% after the intervention. Students demonstrated high interest in the PMR technique as it was easy to understand and could be practiced independently. Progressive muscle relaxation education proved effective in helping students manage academic stress and is recommended to be implemented as part of school mental health programs.